RELASI AGAMA DAN NEGARA (RESPON TERHADAP POLITIK HUKUM ISLAM DI INDONESIA) - Amrin Amrin (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
This article aims to examine the relationship between religion and the state in responding to the politics of Islamic law in Indonesia. The research method uses descriptive qualitative research with literature studies aimed at examining primary data, namely laws, similar regulations, journals, books, and other sources related to research problems. The research approach is social legal research. The technique of data collection with literature study with data analysis with qualitative descriptive methods. The results of the study show that Indonesia is not a religious state but religion is one of the most important elements, so that the relationship between religion and the state has implications for the positivization of Islamic law into national law as a form of state manifestation as a unit that cannot be separated from religious life which is symbiotic- integralistic, by giving birth to a product of Islamic law as a national law until it remains valid. so as to provide harmony, peace, in the life of religion, nation and state is achieved and remains sustainable.